In the kitchen utensils, tools and equipment [videorecording] - Scoglio, Stephen (VEA (Video Education America), 2010)
"Chef Hemi Reidy takes us inside the restaurant kitchen where he weaves his magic for the daily dining pleasure of customers, and presents a lively and comprehensive look at using all sorts of tools, utensils and equipment in the kitchen."